Analisis Terhadap Batasan Adendum Perjanjian Kerjasama Pemerintah dengan Badan Usaha (KPBU) dalam Penyediaan Infrastruktur - Fakhruddin, Husni Muhammad; Fauzi, Wetria; Warman, Kurnia (Nagari Law Review, 2023)
Agreements are one of the domains regulated through private legal instruments. However, agreements are not always governed by private legal instruments. Sometimes, public legal instruments also regulate an agreement, especially when it involves government entities. This study aims to examine the extent to which an addendum to a Public Private Partnership Agreement in Infrastructure Provision can be carried out, considering one of the specifications of the procurement mechanism for implementing business entities in the Public Private Partnership scheme, which includes attaching a draft agreement in the Request for Proposal (RfP) document. After a winning Business Entity is selected, the draft agreement is finalized, with the rule that the substance that has been completed cannot be changed. This research focuses on determining the limitations in making an addendum to the Public Private Partnership Agreement in Infrastructure Provision during the draft agreement's finalization and implementation phase. The research method used in this study is empirical legal research, which utilizes primary and secondary data. KPBU agreements are controlled by private legal instruments and regulated through public legal instruments. Even though some provisions do not allow changing the substance being competed for, these provisions are not norms that can be categorized as lex imperfect because if these provisions deviate, they will automatically injure the principles of procurement. Therefore the procurement is not following the principles regulated in the laws – invitation and may result in a failed auction condition.